2022
DOI: 10.1021/acsomega.2c05550
|View full text |Cite
|
Sign up to set email alerts
|

Property and Reactivity Relationships of Co3O4 with Diverse Nanostructures for Soot Oxidation

Abstract: Cobalt oxide (Co3O4) nanostructures with different morphologies (nanocubes, nanoplates, and nanoflowers) were synthesized by a simple hydrothermal method and used for catalytic oxidation of soot particles. Through the study of the physicochemical properties of the catalysts, the key factors affecting the performance of soot oxidation were investigated. The results showed that all three kinds of Co3O4 nanocrystals exhibited excellent low-temperature activity in catalytic oxidation of soot, and the Co3O4 nanoflo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Interestingly, the methane conversion rate declined with increasing temperature, whereas it rose with decreasing temperature (300~400 • C) under the auspices of the Au-Pd-3.61CoO/3DOM Co 3 O 4 catalyst. Furthermore, the researchers observed that the deactivation of 3DOM Co In conclusion, doping of noble metals can enhance the oxygen activity and stabili of Co-O bond and affect the fracture and formation of Co-O bond, thus raising the con centration of oxygen vacancies [102][103][104]. For instance, doping noble metals such as Pt an Pd can effectively introduce numerous oxygen vacancies while also boosting the Cobond content on composite catalyst material surfaces.…”
Section: Noble Metalsmentioning
confidence: 94%
See 3 more Smart Citations
“…Interestingly, the methane conversion rate declined with increasing temperature, whereas it rose with decreasing temperature (300~400 • C) under the auspices of the Au-Pd-3.61CoO/3DOM Co 3 O 4 catalyst. Furthermore, the researchers observed that the deactivation of 3DOM Co In conclusion, doping of noble metals can enhance the oxygen activity and stabili of Co-O bond and affect the fracture and formation of Co-O bond, thus raising the con centration of oxygen vacancies [102][103][104]. For instance, doping noble metals such as Pt an Pd can effectively introduce numerous oxygen vacancies while also boosting the Cobond content on composite catalyst material surfaces.…”
Section: Noble Metalsmentioning
confidence: 94%
“…After Co loading, the methane combustion catalytic activity was significantly boosted, and SmMn2O5 proved to be the key player in stabilizing the Co3O4 against sintering. This kind of mutual promotion paid off, with the Co/SMO-50% (50% represents the proportion of SmMn2O5) catalyst displaying overall superior catalytic performance with In conclusion, the appropriate amount of metal oxide doping can enhance the oxygen activity and stability of Co-O bond and elevate the concentration of active oxygen [132][133][134][135], thus improving the catalytic efficiency of methane oxidation reaction [102,[136][137][138]. For example, doping of CeO 2 can introduce a large number of oxygen vacancies into the Co In addition, ZrO 2 can also cause lattice distortion, increase surface defects, promote the formation of Co-O bonds, and improve its oxygen activity and stability.…”
Section: Catalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, innovative catalyst materials, such as transition metal oxides and non-noble metal catalysts, have shown promising results in catalyzing soot oxidation while addressing cost and sustainability concerns [68]. Similarly, nanostructured catalyst materials have emerged as a prominent trend in soot oxidation research [69]. Nanostructured catalysts exhibit increased surface area and enhanced catalytic activity, enabling more efficient soot oxidation at lower temperatures.…”
Section: Diversity In Catalysts For Removal Of Sootmentioning
confidence: 99%